1987
DOI: 10.1002/1098-2337(1987)13:4<187::aid-ab2480130403>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Verbal interactions of aggressively and nonaggressively predisposed males in a drinking situation

Abstract: The effects of progressive intoxication were studied in male social drinkers classified from prior histories as either aggressively (A) or nonaggressively (NA) predisposed while intoxicated. Two groups of two A and two NA subjects engaged in videotaped group discussions that were analyzed by Bales interaction process analysis (IPA). At comparable levels of ad libitum alcohol intake in a natural drinking environment, significantly more verbal activity was displayed by the A subjects than by the NA subjects (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…This phenomenon is consistent with research indicating that low testosterone individuals are more active when drinking than when not drinking (Lindman et al, 1987). In the current study, the low testosterone individuals were not only more active, but they also significantly increased their use of Rough strategies while drinking as compared to while they were not drinking.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon is consistent with research indicating that low testosterone individuals are more active when drinking than when not drinking (Lindman et al, 1987). In the current study, the low testosterone individuals were not only more active, but they also significantly increased their use of Rough strategies while drinking as compared to while they were not drinking.…”
Section: Discussionsupporting
confidence: 92%
“…Jeffcoate et al (1986), studying four male physicians aged 28 to 38 who were confined on a boat for a two-week holiday cruise, report T to be correlated with the physicians' assertive and dominant behavior, as ranked by three women also on the boat. Lindman et al (1987), studying 25 men aged 22 to 27, found significantly higher T among those judged by their peers to be most aggressive while drunk. Banks and Dabbs (1996) found higher mean T among 16 young men they classified as "delinquent," based on flamboyant dress, drug use, and violence, than among 15 college men.…”
Section: Dominance and Aggression In Adulthoodmentioning
confidence: 99%
“…Prisoners with high testosterone are more likely to have a history of violent crime and to have other prisoners rate their behavior as more aggressive (Dabbs et al, 1991; Kreuz & Rose, 1972). When behavior ratings are derived from observers, positive relationships between testosterone and dominance or aggression are consistently observable (Jeffcoate et al, 1978; Lindman et al, 1987; Scaramella & Brown, 1978). These and many other findings document that, generally, high levels of testosterone promote the pursuit of dominance and status in socially acceptable ways, but that in some cases they can also lead to aggression, antisocial behavior, and sometimes violent crime (Mazur & Booth, 1998).…”
Section: Relationships Between Implicit Power Motivation Baseline Tementioning
confidence: 99%